Control of Enzymatic Browning in Apple and Potato Purees by Using Guava Extract - Thipnate, Poonsiri; Sukhonthara, Sukhontha (Science, Engineering and Health Studies, 2015)
Control of polyphenol oxidase (PPO) and browning prevention in apple and potato purees by using guava extract (GE) compared with distilled water (DW) were studied at 4 concentrations, including 25%GE (0.24 g wet guava pulp/mL of the extract), 50%GE (0.48 g wet guava pulp/mL of the extract), 75%GE (0.72 g wet guava pulp/mL of the extract), and 100%GE (0.97 g wet guava pulp/mL of the extract). After storage for 5 h, the browning value of apple and potato purees blended with 100%GE was significantly lower than those treated with 50%GE, 25%GE, and DW (p≤0.05). The L* value of apple puree treated with 100%GE was significantly higher than those treated with others (p≤0.05), while L* value of potato puree treated with 100%GE was not significantly higher than that treated with 75%GE (p>0.05), but significantly higher than those treated with others (p≤0.05) during storage. The inhibitions of both PPOs were increased by increasing in guava extracted concentration. The most effectiveness in inhibition of apple and potato PPO activity was 74.53±0.41% and 64.62±0.52%, respectively. Moreover, 100%GE exhibited a higher inhibitory effect on apple PPO than 0.02% w/v citric acid and 0.02% w/v ascorbic acid, while it exhibited a higher inhibitory effect on potato PPO than 0.02% w/v citric acid, and showed similar inhibitory effect to 0.02% w/v ascorbic acid. 100%GE showed the highest total phenolic compound and 0.02% w/v ascorbic acid content values of 880.73±2.15 µg gallic acid equivalent (GAE)/mL sample and 122.67±2.02 µg/mL, respectively. In conclusion, GE possessed effective inhibitors against enzymatic browning in apple and potato purees.